2020
DOI: 10.1021/acs.jctc.9b01274
|View full text |Cite
|
Sign up to set email alerts
|

Describing Polytopal Rearrangements of Fluxional Molecules with Curvilinear Coordinates Derived from Normal Vibrational Modes: A Conceptual Extension of Cremer–Pople Puckering Coordinates

Abstract: In this work a new curvilinear coordinate system is presented for the comprehensive description of polytopal rearrangements of N-coordinate compounds (N = 4–7) and systems containing an N-coordinate subunit. It is based on normal vibrational modes and a natural extension of the Cremer–Pople puckering coordinates (J. Am. Chem. Soc.1975971354) together with the Zou–Izotov–Cremer deformation coordinates (J. Phys. Chem. A20111158731) for ring structures to N-coordinate systems. We demonstrate that the new curvilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 148 publications
0
23
0
Order By: Relevance
“…As a part of our enduring interest in describing the polytopal rearrangement mechanisms with theoretical chemistry, we chose the octacoordinate rhenium polyhydride complexes ReH 5 (PPh 3 ) 2 L (L = pyridine and 2-(acetylamino)­pyridine) as the subject to be investigated in this work. We chose rhenium polyhydrides as the first target in this series of investigations over other octacoordinate compounds because fluxionality in rhenium polyhydrides is a current topic of interest in the experimental organometallic community. …”
Section: Introductionmentioning
confidence: 99%
“…As a part of our enduring interest in describing the polytopal rearrangement mechanisms with theoretical chemistry, we chose the octacoordinate rhenium polyhydride complexes ReH 5 (PPh 3 ) 2 L (L = pyridine and 2-(acetylamino)­pyridine) as the subject to be investigated in this work. We chose rhenium polyhydrides as the first target in this series of investigations over other octacoordinate compounds because fluxionality in rhenium polyhydrides is a current topic of interest in the experimental organometallic community. …”
Section: Introductionmentioning
confidence: 99%
“…From another point of view, this work is an initial assessment of usefulness and advantages of CPCs for the formulation of the NSE. The usefulness of CPCs and RDCs for the construction of n D-PESs (or to perform conformational studies) is well-known, , and new contributions concerning these coordinate systems and their generalization appeared in the literature in the last two years; , therefore, in the opinion of the authors the development and the assessment of computational tools aiming at the employment of these coordinates in a quantum mechanical description of the nuclear motions is worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for the model system 1, we consider the SS-δ-trans and SS-δ-Λ-cis-β stereoisomers of the catalyst in the complexes with (R)-and (S)-enantiomers of propylene oxide (denoted in the following as RPO and SPO). It should be emphasized here that in the present work we focus on the relative stability of the alternative isomers, without considering the possible interconversion reactions between these complexes, such as e.g., nondissociative ligand exchange processes [63][64][65][66][67]. Our previous results for simple Co(III)-salcy complexes [51] indicated that trans ↔ cis-β interconversions can be characterized by relatively low barriers (13-15 kcal/mol), but they involve disfavored pentacoordinated trans species.…”
Section: Considered Models and Stereoisomersmentioning
confidence: 95%